MASTER-APPRENTICE RELATIONSHIP OF GREAT TARIQAH REPRESENTATIVES (Academicia Globe: Inderscience Research, 2021)
The article reveals some aspects of relations between Alisher Navoi and Abdurakhman Djami as an apprentice of the great pir of tariqah naqshbandiy.